2004
DOI: 10.1128/jvi.78.16.8477-8485.2004
|View full text |Cite
|
Sign up to set email alerts
|

Initial Cleavage of the Human Immunodeficiency Virus Type 1 GagPol Precursor by Its Activated Protease Occurs by an Intramolecular Mechanism

Abstract: Processing of the GagPol polyprotein precursor of human immunodeficiency virus type 1 (HIV-1) is a critical step in viral assembly and replication. The HIV-1 protease (PR) is translated as part of GagPol and is both necessary and sufficient for precursor processing. The PR is active only as a dimer; enzyme activation is initiated when the PR domains in two GagPol precursors dimerize. The precise mechanism by which the PR becomes activated and the subsequent initial steps in precursor processing are not well un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
158
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(172 citation statements)
references
References 54 publications
14
158
0
Order By: Relevance
“…Moreover, they showed that competitive active site inhibition by the drug retonavir was 10,000-fold less for the protease embedded in the precursor than for the mature free protease (20). Earlier, kinetic studies on the model precursor system MBP-⌬TF-Protease-⌬RT showed that the protease maturation takes place in two steps.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they showed that competitive active site inhibition by the drug retonavir was 10,000-fold less for the protease embedded in the precursor than for the mature free protease (20). Earlier, kinetic studies on the model precursor system MBP-⌬TF-Protease-⌬RT showed that the protease maturation takes place in two steps.…”
mentioning
confidence: 99%
“…Pettit et al (20) have recently shown, by co-expressing equivalent amounts of substituted Gag-Pol constructs, that the initial cleavage of the HIV-1 Gag-Pol precursor is intramolecular. Moreover, they showed that competitive active site inhibition by the drug retonavir was 10,000-fold less for the protease embedded in the precursor than for the mature free protease (20).…”
mentioning
confidence: 99%
“…The first cleavage site is located between sp1 and NC, and the second is inside the p6* region of the GagPol precursor polyprotein, divinding p6* in an octapeptide (sometimes referred as Transframe Peptide, TFP) and a 48 amino acids region that is immediately upstream the PR. These two cleavages generate the processing intermediates MA-CA-sp1 (42KDa), NC-TFP (7,4KDa) from Gag and p6*-PR-RT-IN (113KDa) from Pol (Pettit et al, 2004). It is thought that at this point p6* acts as a zymogen, lying on the catalityc center and blocking further cleavages (Partin et al, 1991).…”
Section: Nef and Virus Maturationmentioning
confidence: 99%
“…Other feature is that the cleavage sites recognized by HIV and SIV PR do not share amino acid identity on the cleavage sequence, or on its flanking regions (Hellen et al, 1989;Krausslich et al, 1988). Finally, the last characteristic that separate HIV and SIV PR from its cellular relatives is that, as for cellular PRs the whole catalytic machinery is pre-formed, and its activation lies mostly on the cleavage of a zymogen (Tang and Wong, 1987), for HIV and SIV PR the activation is extremely controlled by mechanisms involving protein folding, zymogen cleavage, PR context, interactions and pH (Gatlin et al, 1998;Partin et al, 1991;Pettit et al, 2004). These abundant regulatory mechanisms point out that the correct PR activation is essential for the formation of infectious particles, and that a premature activation must be avoided.…”
Section: Nef and Virus Maturationmentioning
confidence: 99%
See 1 more Smart Citation